Repeated Measurement of Absolute and Relative Judgments of Loudness: Clinical Relevance for Prescriptive Fitting of Aided Target Gains for soft, Comfortable, and Loud, But Ok Sound Levels - Formby, Craig; Payne, JoAnne; Yang, Xin; Wu, Delphanie; Parton, Jason M. (Seminars in Hearing, 2017)
This study was undertaken with the purpose of streamlining clinical measures of loudness growth to facilitate and enhance prescriptive fitting of nonlinear hearing aids. Repeated measures of loudness at 500 and 3,000 Hz were obtained bilaterally at monthly intervals over a 6-month period from three groups of young adult listeners. All volunteers had normal audiometric hearing sensitivity and middle ear function, and all denied problems related to sound tolerance. Group 1 performed judgments of soft and loud, but OK for presentation of ascending sound levels. We defined these judgments operationally as absolute judgments of loudness. Group 2 initially performed loudness judgments across a continuum of seven loudness categories ranging from judgments of very soft to uncomfortably loud for presentation of ascending sound levels per the Contour Test of Loudness; we defined these judgments as relative judgments of loudness. In the same session, they then performed the absolute judgments for soft and loud, but OK sound levels. Group 3 performed the same set of loudness judgments as did group 2, but the task order was reversed such that they performed the absolute judgments initially within each test session followed by the relative judgments. The key findings from this study were as follows: (1) Within group, the absolute and relative tasks yielded clinically similar judgments for soft and for loud, but OK sound levels. These judgments were largely independent of task order, ear, frequency, or trial order within a given session. (2) Loudness judgments increased, on average, by ∼3 dB between the first and last test session, which is consistent with the commonly reported acclimatization effect reported for incremental changes in loudness discomfort levels as a consequence of chronic bilateral hearing aid use. (3) Measured and predicted comfortable judgments of loudness were in good agreement for the individual listener and for groups of listeners. These comfortable judgments bisect the measured levels judged for soft and for loud, but OK sounds. (4) Loudness judgments within the same loudness category varied across listeners within group by as much as 50 to 60 dB. Such large variation in judgments of loudness is problematic, especially because hearing-impaired listeners are known to exhibit similarly large ranges of intersubject response variation and, yet, poplar prescriptive fitting strategies continue to use average rather than individual loudness data to fit nonlinear hearing aids. The primary conclusions drawn from these findings are that reliable absolute judgments of soft and loud, but OK are clinically practical and economical to measure and, from these judgments, good estimates of comfortable loudness can also be predicted for individuals or for groups of listeners. Such loudness data, as measured as described in this report, offer promise for streamlining and enhancing prescriptive fitting of nonlinear hearing aids to target gain settings for soft (audible), comfortable, and loud, but OK (tolerable) sound inputs for the individual listener.
Keywords: Absolute and relative loudness judgments; loudness growth; repeated measures